2012
DOI: 10.1021/la301222m
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Structure Variation on Solution Properties of Hydrotropes: Phenyl versus Cyclohexyl Chain Tips

Abstract: Link to publication record in Explore Bristol Research PDF-document This is the author accepted manuscript (AAM). The final published version (version of record) is available online via ACS at http://pubs.acs.org/doi/abs/10.1021/la301222m. Please refer to any applicable terms of use of the publisher. University of Bristol -Explore Bristol Research General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
3
7
0
Order By: Relevance
“…Results that confirm this evidence were obtained, for instance, with the non-aromatic [C 4 C 1 pip]Cl and [C 4 C 1 pyrr]Cl. This is in good agreement with various authors 8,13,64,65 that have previously ruled out π…π interactions as the dominant effect governing the hydrotropy. This trend also discards the possibility that the hydrotropy of ILs could be related to clathrate formation as proposed by Rogers and co-workers 66,67 and Rebelo and co-workers 68,69 to explain the enhanced solubility of benzene in pure aromatic ILs.…”
Section: Resultssupporting
confidence: 93%
“…Results that confirm this evidence were obtained, for instance, with the non-aromatic [C 4 C 1 pip]Cl and [C 4 C 1 pyrr]Cl. This is in good agreement with various authors 8,13,64,65 that have previously ruled out π…π interactions as the dominant effect governing the hydrotropy. This trend also discards the possibility that the hydrotropy of ILs could be related to clathrate formation as proposed by Rogers and co-workers 66,67 and Rebelo and co-workers 68,69 to explain the enhanced solubility of benzene in pure aromatic ILs.…”
Section: Resultssupporting
confidence: 93%
“…Hydrotropic salts have shown to be successful in elongating spherical reverse micellar structures to form rod-like and ellipsoid microemulsions in alkanes, and also interestingly scCO 2 systems [40,94,104]. Extensive work by Hatzopoulos et al has been carried out to investigate further the impacts of hydrotropic salt structure and water level ( w ) on AOT surfactant microemulsion structure in w / o systems [40,105106]; these findings were used as the basis for designing CO 2 -philic analogues. James et al studied the impacts of w value and hydrotrope concentration in water-in-oil ( w / o ) and in water-in-scCO 2 ( w / c ) systems using universal surfactant TC14 [94].…”
Section: Reviewmentioning
confidence: 99%
“…The cyclohexane derivative 12 exhibits a higher CMC than its phenyl counterpart 13 , whereas the surface tension of water could be decreased much lower (Table , entries 1 and 2). Hatzopoulos et al reported this trend comparing very short phenyl and cyclohexyl n -alkanoates ( n = 0 and 1) . For these molecules the hydrophobic contribution of the phenyl group is higher than the cyclohexyl compound, as observed for compounds 12 and 13 .…”
Section: Resultsmentioning
confidence: 77%
“…Hatzopoulos et al reported this trend comparing very short phenyl and cyclohexyl n-alkanoates (n = 0 and 1). 45 For these molecules the hydrophobic contribution of the phenyl group is higher than the cyclohexyl compound, as observed for compounds 12 and 13. Tetraols 14−18 bearing a linear alkyl chain with increasing length were next considered.…”
mentioning
confidence: 69%